Music and Disorders of Consciousness: Emerging Research, Practice and Theory - Barbara Tillmann (Frontiers Research Topics, 2017)
Music processing in severely brain-injured patients with disorders of consciousness has been an emergent field of interest for over 30 years, spanning the disciplines of neuroscience, medicine, the arts and humanities. Disorders of consciousness (DOC) is an umbrella term that encompasses patients who present with disorders across a continuum of consciousness including people who are in a coma, in vegetative state (VS)/have unresponsive wakefulness syndrome (UWS), and in minimally conscious state (MCS). Technological developments in recent years, resulting in improvements in medical care and technologies, have increased DOC population numbers, the means for investigating DOC, and the range of clinical and therapeutic interventions under validation. In neuroimaging and behavioural studies, the auditory modality has been shown to be the most sensitive in diagnosing awareness in this complex population. As misdiagnosis remains a major problem in DOC, exploring auditory responsiveness and processing in DOC is, therefore, of central importance to improve therapeutic interventions and medical technologies in DOC. In recent years, there has been a growing interest in the role of music as a potential treatment and medium for diagnosis with patients with DOC, from the perspectives of research, clinical practice and theory. As there are almost no treatment options, such a non-invasive method could constitute a promising strategy to stimulate brain plasticity and to improve consciousness recovery. It is therefore an ideal time to draw together specialists from diverse disciplines and interests to share the latest methods, opinions, and research on this topic in order to identify research priorities and progress inquiry in a coordinated way. This Research Topic aimed to bring together specialists from diverse disciplines involved in using and researching music with DOC populations or who have an interest in theoretical development on this topic. Specialists from the following disciplines participated in this special issue: neuroscience; medicine; music therapy; clinical psychology; neuromusicology; and cognitive neuroscience.